Influence of congenital human cytomegalovirus infection and the NKG2C genotype on NK‐cell subset distribution in children - Noyola, Daniel E.; Fortuny, Claudia; Muntasell, Aura; Noguera‐Julian, Antoni; Muñoz‐Almagro, Carmen; Alarcón, Ana; Juncosa, Teresa; Moraru, Manuela; Vilches, Carlos; López‐Botet, Miguel (European journal of immunology, 2012)
Human cytomegalovirus (HCMV) has been reported to reshape the NK‐cell receptor (NKR) distribution, promoting an expansion of CD94/NKG2C+ NK and T cells. The role of NK cells in congenital HCMV infection is ill‐defined. Here we studied the expression of NKR (i.e., NKG2C, NKG2A, LILRB1, CD161) and the frequency of the NKG2C gene deletion in children with past congenital infection, both symptomatic (n = 15) and asymptomatic (n = 11), including as controls children with postnatal infection (n = 11) and noninfected (n = 20). The expansion of NKG2C+ NK cells in HCMV‐infected individuals appeared particularly marked and was associated with an increased number of LILRB1+ NK cells in cases with symptomatic congenital infection. Increased numbers of NKG2C+, NKG2A+, and CD161+ T cells were also associated to HCMV infection. The NKG2C deletion frequency was comparable in children with congenital HCMV infection and controls. Remarkably, the homozygous NKG2C+/+ genotype appeared associated with increased absolute numbers of NKG2C+ NK cells. Moreover, HCMV‐infected NKG2C+/+ children displayed higher absolute numbers of NKG2A+ and total NK cells than NKG2C+/− individuals. Our study provides novel insights on the impact of HCMV infection on the homeostasis of the NK‐cell compartment in children, revealing a modulatory influence of NKG2C copy number.